Perbuatan Melawan Hukum Berupa Pelanggaran Hak Cipta Terhadap Pemegang Lisensi Hak Cipta (Studi Putusan Nomor 02/PDT.SUS-HKI/2015/PN/NIAGA.Smg jo. Putusan Nomor 518 K/Pdt.Sus-HKI/2015 jo. Putusan Nomor 43 PK/Pdt.Sus-HKI/2017) - Eko Rial Nugroho; Wahyu Priyanka NP (Fakultas Hukum Universitas Islam Indonesia, 2020)
PT. ISM and FIFA signed a license agreement on 5 May 2011, relating to the assignment of certain media rights incurred in connection with the XX edition of the football tournament and other FIFA events. Based on this exclusivity, no other party (including but not limited to broadcasters), has the right to (but is not limited to) socializing, marketing and monitoring the license to use the 2014 Brazil World Cup broadcast commercially in commercial places. However, there are parties, namely PT. MHIS which is suspected of committing acts without rights, broadcasting or broadcasting or holding activities to watch the 2014 Brazil World Cup together commercially and does not have a license permit from PT. ISM. As a result of the 2014 Brazil World Cup broadcast by PT. MHIS the PT. ISM feels disadvantaged both materially and immaterially. The purpose of this research is to find out whether the perpetrators of copyright infringement can be categorized as acts against the law and how the legal protection of copyright license holders for unlawful acts of copyright infringement. This research is a normative legal research using qualitative analysis. This study concludes that PT. MHIS has committed unlawful acts in the form of Copyright infringement and legal protection for Copyright license holders by taking legal action in the form of a lawsuit to the Commercial Court and asking for compensation for unlawful acts committed by PT. MHIS.